Kedisiplinan Kerja Karyawan pada PT. Gemilang Prima Utama - Risda Rahmayani; Palahudin Palahudin (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Work discipline is a fundamental element of human resource management that influences employee behavior and organizational effectiveness. In practice, weaknesses in work discipline may result in deviations from work standards, unethical conduct, and noncompliance with organizational regulations. This study aims to describe the level of employee work discipline at PT. Gemilang Prima Utama and to identify the most dominant indicators of disciplinary violations based on established work discipline criteria. This research employed a quantitative descriptive approach using internal company data collected during the Field Work Practice (Kuliah Kerja Lapangan) period from January to October 2025. Data were obtained through direct observation and documentation of disciplinary violation records. The analysis was conducted by classifying violation cases according to five work discipline indicators: attendance, compliance with work regulations, compliance with work standards, work alertness, and ethical work behavior. The results indicate that a total of 40 disciplinary violation cases were recorded. The most frequent violations occurred in compliance with work standards (35%), followed by ethical work behavior (30%) and compliance with work regulations (25%). Attendance-related violations accounted for 10% of cases, while no violations were found in the work alertness indicator. These findings suggest that disciplinary issues at PT. Gemilang Prima Utama are more closely related to work quality and ethical behavior than to attendance. Strengthening supervision, work standard implementation, and ethical guidance is therefore essential to improving employee work discipline.